2020
DOI: 10.1038/s41598-020-73568-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between a common Caribbean corallivorous snail and protected area status, coral cover, and predator abundance

Abstract: As coral populations decline across the Caribbean, it is becoming increasingly important to understand the forces that inhibit coral survivorship and recovery. Predation by corallivores, such as the short coral snail Coralliophila abbreviata, are one such threat to coral health and recovery worldwide, but current understanding of the factors controlling corallivore populations, and therefore predation pressure on corals, remains limited. To examine the extent to which bottom-up forces (i.e., coral prey), top-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
(94 reference statements)
1
2
0
Order By: Relevance
“…Lastly, grazing snails (i.e., smooth tegula and green nerite) also seemed to be most active and abundant at night, which suggests many wounds are produced nocturnally and could explain why this phenomenon has been overlooked (i.e., most seagrass research takes place during the day). This also suggests that nocturnal predators, such as grunts and octopus, may have the ability to control grazing snail populations in seagrass systems, similar to what has been shown for snails on coral reefs (Shaver et al, 2020).…”
Section: Discussionsupporting
confidence: 62%
“…Lastly, grazing snails (i.e., smooth tegula and green nerite) also seemed to be most active and abundant at night, which suggests many wounds are produced nocturnally and could explain why this phenomenon has been overlooked (i.e., most seagrass research takes place during the day). This also suggests that nocturnal predators, such as grunts and octopus, may have the ability to control grazing snail populations in seagrass systems, similar to what has been shown for snails on coral reefs (Shaver et al, 2020).…”
Section: Discussionsupporting
confidence: 62%
“…Marine protected areas may indirectly provide some resilience against disease by protecting corallivore predator populations, conserving biodiversity, reducing macroalgae, and limiting fishing activity. One study from the Philippines found that fish biodiversity was higher in protected areas, where disease prevalence was lower (Raymundo et al 2009) and surveys in the Florida Keys found that protected areas had more diverse corallivore predator assemblages, which was correlated with decreased C. galea (i.e., abbreviata) abundance (Shaver et al 2020). It may be that marine protected areas with more robust corallivore predator assemblages indirectly decrease disease prevalence by controlling corallivore populations (Fig.…”
Section: Interactions Among Corallivores Disease and Noncorallivore S...mentioning
confidence: 98%
“…To maintain sufficient coral cover on recently established ARs, reducing coral predation directly through AR design or outplanted species selection appears more effective than attempting to regulate corallivore populations indirectly by facilitating their predators. This suggestion applies in particular to larger adult corallivores, which are less sensitive to predation (Cowan et al, 2017;Shaver et al, 2020). Excess nutrient inputs by humans are generally detrimental to reef functioning and could promote corallivores (Shantz and Burkepile, 2014;Pratchett et al, 2017), but nutrient recycling by fish communities has been shown to benefit corals on natural reefs (Shantz et al, 2015) and might help to facilitate recovery of degraded reefs (Ladd and Shantz, 2020).…”
Section: Ecological Facilitationmentioning
confidence: 99%